Nghiên cứu thu nhận antimon từ quặng antimon bằng axit clohydric - Nhiệm, Đào Ngọc; Chức, Phạm Ngọc; Dũng, Đoàn Trung; Hà Chi, Nguyễn Thị; Văn, Nguyễn Đức (Vietnam Journal of Chemistry, 2015)
The separation and recovery of antimony from the Tan Lac – Hoa Binh antimony ore by hydrochloric acid has been studied. The effects of acid concentration, the rate of acid /ore and time effect on the recovery coefficient recovery of antimony have been studied. The results indicated that the recovery coefficient of antimony was enhanced from 6.25 % to 30 % with a reactive high yield of 87-89 % by using optimum conditions: the ratio of antimony acid / ore = 3:1; reaching time effect of 8 hours and HCl concentration of 6 M.